Purification and biochemical characterization of two xylanases produced by Aspergillus caespitosus and their potential for kraft pulp bleaching - Sandrim, V. C. [UNESP]; Rizzatti, A. C S; Terenzi, H. F.; Jorge, J. A.; Milagres, A. M F; Polizeli, M. L T M (Elsevier, 2005)
Two extracellular xylanases produced by the thermotolerant fungus Aspergillus caespitosus grown in sugar cane bagasse were purified and characterized. Estimated molecular masses were 26.3 and 27 kDa (xyl I); 7.7 and 17.7 kDa (xyl II) for gel filtration and SDS-PAGE, respectively. Optimal temperature for both xylanases was 50-55°C. Optimal pH was 6.5-7.0 for xyl I, and 5.5-6.5 for xyl II. The thermostability (T half) at 55°C was 27.3 min (xyl I) and >90 min (xyl II). Xylanase activity was inhibited by several ions. β-mercaptoethanol activated 59 and 102% xyl I and xyl II activities, respectively. These enzymes preferentially hydrolyzed birchwood xylan, and the K m and V max values were 2.5 mg/ml and 1679 U/mg protein (xyl I), and 3.9 mg/ml and 113 U/mg protein (xyl II). The action of both xylanases mainly that of xyl II, on kraft pulp reduced kappa number and increased pulp viscosity. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Aspergillus caespitosus; Pulp bleaching; Xylanases; Bagasse; Biochemistry; Bleaching; Characterization; Ethanol; Filtration; Fungi; Kraft pulp; Purification; Sugar cane; Thermal effects; Viscosity; Biochemical characterization; Gel filtration; Molecular masses; Optimal temperatures; Xylanase activity; Enzymes; Arundinaria; Aspergillus; Saccharum hybrid cultivar